Effectiveness of transcutaneous electrical nerve stimulation and microcurrent electrical nerve stimulation in bruxism associated with masticatory muscle pain - A comparative study - Rajpurohit Bharat; Khatri Subhash; Metgud Deepa; Bagewadi Anjana (Wolters Kluwer Medknow Publications, 2010)
Objectives: To compare the effectiveness of transcutaneous electrical nerve stimulation (TENS) and microcurrent electrical nerve stimulation (MENS) on masticatory muscles pain bruxism patient. Materials and Methods : A total of 60 subjects with the clinical diagnosis of bruxism were randomly allocated to two study groups. Group A received TENS (50 Hz, pulse width 0.5 mSec, intensity 0-60 mA for 20 minutes for a period of seven days) and Group B received MENS (0.5 Hz, intensity 1,000 μA for 20 minutes for a period of seven days). The outcome measures were assessed in term of Visual Analog Scale (VAS) and digital pressometer of 2 Kgf. Results : The study showed significant change in intensity of pain as per VAS score ( P ≤ 0.0001) and tenderness as per digital pressometer ( P ≤ 0.0001). Conclusion : MENS could be used as an effective pain-relieving adjunct to TENS in the treatment of masticatory muscle pain due to bruxism.